Pengaruh Ragi dan Lama Fermentasi Terhadap Mutu Kimia dan Organoleptik pada Tape Biji Barley: Effect of Yeast Concentration and Fermentation Time on pH, Alcohol Content, and Organoleptic Quality of Barley Seed Tapai - Kurniasih, Lilis Risma; Fauziyyah, Athiefah (Jurnal Teknologi dan Mutu Pangan, 2024)
Tapai is one of Indonesia’s traditional foods, made from fermented carbohydrate-containing food materials such as cassava and sticky rice. Barley seeds are one of the food materials that are rarely utilized and contain carbohydrates so that they can be used as raw materials in making tape. The purpose of this study was to determine how the pH value, alcohol content and organoleptic quality of barley seed tape can be influenced by variations in yeast concentration and fermentation time during the processing process. The research method used was a complete randomized design (CRD) test with two variables: variations in yeast concentration (0.5 grams, 1.0 gram and 1.5 grams) and fermentation time (24 hours, 48 hours, and 72 hours). The results showed that different yeast concentrations significantly affected the pH value, alcohol content, and organoleptic quality of barley tape. Both pH value and organoleptic quality were significantly affected by the length of fermentation but had no effect on alcohol content. Barley seed tape with a yeast concentration of 0.5 grams and a fermentation time of 48 hours was the treatment combination most favored by panelists and had good tape quality. The research contributes to opening opportunities for diversification of traditional food ingredients that were previously rarely utilized.